2015
DOI: 10.3389/fncom.2015.00110
|View full text |Cite
|
Sign up to set email alerts
|

Modeling spontaneous activity across an excitable epithelium: Support for a coordination scenario of early neural evolution

Abstract: Internal coordination models hold that early nervous systems evolved in the first place to coordinate internal activity at a multicellular level, most notably the use of multicellular contractility as an effector for motility. A recent example of such a model, the skin brain thesis, suggests that excitable epithelia using chemical signaling are a potential candidate as a nervous system precursor. We developed a computational model and a measure for whole body coordination to investigate the coordinative proper… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 40 publications
(52 reference statements)
1
12
0
Order By: Relevance
“…Remarkably, Burr even partially anticipated the computational neuroscience techniques being applied to nonneural bioelectricity (Friston et al 2015;Pezzulo and Levin 2015), by inquiring about the design principles of the brain and its information-processing functions (as distinct from the implementation mechanisms). Consistently with Burr's ideas of the evolutionary process shaping brain and somatic tissues, it is now increasingly beginning to be appreciated how neural computation evolved by speed-optimizing information processing tasks that cells were already doing long before nervous systems evolved (Keijzer et al 2013;de Wiljes et al 2015;Jekely et al 2015;Keijzer 2017;Keijzer and Arnellos 2017;Fields et al 2020).…”
Section: Bioelectricity: State Of the Artmentioning
confidence: 81%
“…Remarkably, Burr even partially anticipated the computational neuroscience techniques being applied to nonneural bioelectricity (Friston et al 2015;Pezzulo and Levin 2015), by inquiring about the design principles of the brain and its information-processing functions (as distinct from the implementation mechanisms). Consistently with Burr's ideas of the evolutionary process shaping brain and somatic tissues, it is now increasingly beginning to be appreciated how neural computation evolved by speed-optimizing information processing tasks that cells were already doing long before nervous systems evolved (Keijzer et al 2013;de Wiljes et al 2015;Jekely et al 2015;Keijzer 2017;Keijzer and Arnellos 2017;Fields et al 2020).…”
Section: Bioelectricity: State Of the Artmentioning
confidence: 81%
“…Developed by Keijzer in opposition to the classical reflex arc of pain described by Descartes, this approach shows that it represents probably a secondary adaptation and that biological information processing can occur without CNS in early organisms. Consequently, he describes the myoepithelium or an excitable epithelia using chemical signaling as a primitive conductive element able to transmit information through neuromuscular junctions and motor coordination before the evolution of nervous systems (Keijzer, Wiljes et al 2015) [64,65].…”
Section: The Evolutionary Taxonomy Of Cognitive Controlmentioning
confidence: 99%
“…This thesis supported by Parkers' phylogenetic work about elementary nervous systems (1919) [66] is important because it admits two consequences corresponding to our pioneering discovery on plant spontaneous Kalanchoë electrophytograms (Debono & Bouteau, 1992) [5]: 1/ the presence of a spontaneous activity capable of supporting self-organized whole body organization; 2/ the generation, at the same level of description of animal protomyocytes or neuromuscular processes (Mckie, 1990) [67] and of plant dynamic protoneural networks [6] forming coordinated patterns of activities (illustrated by Wiljes for the tube-shaped animal model) [65].…”
Section: The Evolutionary Taxonomy Of Cognitive Controlmentioning
confidence: 99%
“…Myoepithelia with direct electrical connections by means of gap junctions between the epithelial cells exist in various extant animals, such as cnidarians [33,34]. Here, we build on the hypothesis that proto-neuralia could have possessed myoepithelia with similar electrical connections or with chemical signalling to conduct electrical activity from one cell to the next, by either juxtacrine signalling or basic chemical synapses [30,35,36]. Importantly, this configuration could have provided a scaffold to bring separate pre-and postsynaptic elements in adjacent cells together as a full synapse.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier modelling showed that body topology is a crucial factor here [36]: body-tubes with a high length to width ratio enabled ring-shaped activity patterns travelling along the length of the tube, while a ring-shaped topology induced patterns travelling along the ring's circumference. In the present study, we only used a tube-shaped topology (a) as this particular configuration is generally plausible as a basic animal shape; (b) as a single example would be sufficient to make a case for the potential evolutionary relevance of short and random proto-neural elongations; and (c) by focusing on a single topology we could better focus on the relevance and impact of many different features of the elongations themselves, as will be discussed below.…”
Section: Introductionmentioning
confidence: 99%